Sweeties. #2, Summer/Coco - Grisseaux, Veronique (Charmz, 2019)
Thirteen-year-old Summer is determined to get accepted into a ballet school. But she begins to worry about her figure and takes unhealthy measures to stay thin. Her sisters try their best to help her even though Summer won't admit she has a problem.